Epidemiology of judo-related injuries in 21 seasons of competitions in France: A prospective study of relevant traumatic injuries - Frey, A.; Lambert, C.; Vesselle, B.; Rousseau, R.; Dor, F.; Marquet, L. A.; Toussaint, J. F.; Daoud Crema, M. (Orthopaedic Journal of Sports Medicine, 2019)
Background: Judo is a full-contact fighting sport that may lead to severe injuries. There are limited data available on the incidence of judo-related injuries. The French Judo Federation has established a surveillance system to document the frequency and type of injuries during judo competitions. Purpose: To describe the incidence rates and types of judo-related traumatic injuries during 21 seasons of competitions in France with respect to athlete (judoka) age, sex, and level of performance. Study Design: Descriptive epidemiology study. Methods: Between 1993 and 2014, each physician in charge of each judo competition filled out a form in which he/she documented the number of competing judokas, the number of fights, the number of medical interventions, the specific type of traumatic injuries for each intervention, the number of fight interruptions, and the number of athletes removed from the competition venue because of an injury. The age, sex, and level of performance of each judoka were also documented. Variance analysis was applied to assess whether differences in incidence rates of injuries between groups were significant (Student t test and chi-square test). Results: Surveillance of 421,670 fights demonstrated 3511 injuries in 316,203 judokas (incidence proportion, 1.1%). Among the injuries recorded, the most common were sprains (54.3%), fractures (15.6%), and dislocations (12.5%). Female athletes exhibited significantly higher incidence rates for knee sprains and elbow dislocations, whereas male athletes exhibited a higher incidence rate for shoulder dislocations (P < .001 for all). Regarding age, higher incidence rates were observed in young adults (aged 18-20 years) for acromioclavicular sprains and in children (aged 10-14 years) for clavicle fractures compared with adults (aged 21-35 years) (P < .001 for both). Both young adult and adult athletes had a higher incidence rate of shoulder dislocations (P < .001). Regarding the level of performance, athletes competing at higher levels had a higher incidence rate of sprains to the knee (P < .001). Conclusion: During 21 years of surveillance of injuries in judo competitions in France, the incidence proportion of injuries was 1.1%. Significant differences in incidence rates demonstrated when considering age, sex, and level of performance may help in developing strategies to prevent traumatic injuries in the future.